Gerakan Lansia Sadar Hipertensi: Edukasi Kesehatan Pengendalian Tekanan Darah di Desa Manisharjo - Qothrunnadaa Fajr Rooiqoh; Calisa Dhea Afifah; Kartika Miftahur Rohmah; Diena Rosa Sabila Haque; Fitria Rohma Muthmainah; Zahwa Zahrotul Afifah; Nadin Dikania Abriela; Taskia Ruzaina Hamidah; Salwa Aurellia Nadine; Iva Nurfatimah (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2026)
Hypertension is one of the non-communicable diseases that is a major health problem among the elderly because it is often asymptomatic but can cause serious complications. This activity aims to increase the knowledge and health behavior of the elderly through hypertension education at several health posts in Manisharjo Village. The activity was carried out in February 2026, targeting elderly people who actively participate in routine check-ups at the health posts. The methods used included blood pressure measurements, nutritional status assessments, and educational sessions using informative posters, accompanied by pre-tests and post-tests to measure participants' knowledge levels. The screening results showed that of the 40 elderly people examined, 70% had hypertension, with 38% having stage 1 hypertension and 33% having stage 2 hypertension, while 17% were pre-hypertensive and 12% were normal. The evaluation results showed an increase in the knowledge of the elderly after being given education. This activity demonstrates that posyandu-based education is effective as a promotional and preventive measure in controlling hypertension in the elderly